Studying first-strike stability with knowledge-based models of human decisionmaking - Davis, Paul K., 1943-; Rand Corporation; Rand/UCLA Center for the Study of Soviet International Behavior; Carnegie Corporation of New York. (Santa Monica, CA : RAND, 1989)
First-strike stability depends on the improbability of crises and the improbability that crises would result in first strikes. This study focuses on the latter criterion, which in turn depends on crisis decisionmaking by human beings. The report argues that efforts to understand and improve first-strike stability should be guided by a formal theory of human decisionmaking that accounts for behavioral factors such as mindset, desperation, fatalism, perceptions, and fears. The author identifies three principal mechanisms for improving first-strike stability: (1) improve force-posture stability; (2) review and adjust nuclear policies and doctrine, and the way they are discussed; and (3) improve the likely quality of crisis decisionmaking through efforts involving education, exercises, and staffing.
"April 1989."
"Project on avoiding nuclear war: managing conflict in the nuclear age."
"RAND/UCLA Center for the Study of Soviet International Behavior."
Includes bibliographical references (p. 93-100).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: First strike (Nuclear strategy); Nuclear crisis stability; Nuclear warfare -- Decision making